Efektivitas Pembelajaran Geografi Berbasis Apple Ecosystem dalam Meningkatkan Kemampuan Problem Solving pada Materi Astronomi Posisi dalam Pembinaan Olimpiade Sains - Lukman Samatowa; Masruroh Masruroh; Moch Rio Pambudi (Geosfera: Jurnal Penelitian Geografi, 2025)
Physical geography learning in positional astronomy topics requires strong spatial visualization and problem-solving skills; however, conventional instructional approaches often fail to adequately facilitate these needs. This study aims to analyze the effectiveness of using the Apple ecosystem in improving students’ problem-solving abilities within olympiad training on positional astronomy topics. The research employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group model. The sample consisted of two groups of senior high school students in Gorontalo Province: an experimental group utilizing the Apple ecosystem and a control group receiving conventional instruction. Data were collected through problem-solving ability tests and analyzed using descriptive and inferential statistics. The findings indicate that the experimental group demonstrated a higher improvement in problem-solving skills compared to the control group. The use of the Apple ecosystem enabled visualization of solar positions, simulation of geographic coordinates, and interactive exploration of astronomical phenomena, which supported students in understanding abstract concepts. Technology-enhanced learning environments also increased learning engagement and analytical abilities in solving geography-related problems. These results suggest that structured digital technology integration can strengthen positional astronomy learning through more visual and exploratory learning experiences. This study implies that technology-based strategies can enhance olympiad training and contribute to the advancement of geography education aimed at developing higher-order thinking skills.